2009
DOI: 10.1016/j.icarus.2008.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative compositional analysis of martian mafic regions using the MEx/OMEGA reflectance data

Abstract: The primary objectives of this paper are to determine the modal mineralogy of selected low albedo terrains of different ages ranging from Noachian to Amazonian exposed on the surface of Mars. This analysis is conducted using the spectral modeling of the Observatoire pour la Minéralogie, l'Eau, les Glaces, et l'Activité (OMEGA) reflectance data. Results from this work are consistent with the major results of previous spectroscopic studies: plagioclase (40-60% in volume) and high calcium pyroxene (20-40%, HCP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 84 publications
9
91
0
1
Order By: Relevance
“…This modal mineralogy is typical of mafic magmatic rocks, which could be classified as gabbro-norites with minor amount of olivine for plutonic rocks; the volcanic equivalent nomenclature is two-pyroxene basalt. A decrease of the Low Calcium Pyroxene abundance through time is also observed [15]. The modal mineralogy of areas analyzed here clearly indicates an affinity with some of the basaltic Martian meteorites; they have young crystallization ages, suggesting that they are samples of young (dust-covered) volcanic centers such as Tharsis or Elysium.…”
Section: Applicationsupporting
confidence: 56%
See 1 more Smart Citation
“…This modal mineralogy is typical of mafic magmatic rocks, which could be classified as gabbro-norites with minor amount of olivine for plutonic rocks; the volcanic equivalent nomenclature is two-pyroxene basalt. A decrease of the Low Calcium Pyroxene abundance through time is also observed [15]. The modal mineralogy of areas analyzed here clearly indicates an affinity with some of the basaltic Martian meteorites; they have young crystallization ages, suggesting that they are samples of young (dust-covered) volcanic centers such as Tharsis or Elysium.…”
Section: Applicationsupporting
confidence: 56%
“…The derivation of the modal mineralogy of unaltered mafic-rich regions allows to evaluate constraints on the chemistry and petrology of the ancient crust, and to explore how crustal components might have arisen on Mars. OMEGA modal derived analyses [15] indicate a basaltic composition for all of the low albedo extended regions (Fig. 3).…”
Section: Applicationmentioning
confidence: 92%
“…The martian meteorites appear to be depleted in aluminum (or plagioclase), sodium, potassium, and thorium relative to both in-situ measurements of rocks and soils of materials at the Gusev, Meridiani, Gale, and Mars Pathfinder landing sites and with orbital gamma ray spectrometer and near-infrared spectroscopy observations (McSween et al, 2009;Poulet et al, 2009;Treiman and Filiberto, 2015). These differences in magma composition may reflect temporal changes in the water content, oxidation state, or temperature of the mantle over time (Balta and McSween, 2013;Baratoux et al, 2013;Tuff et al, 2013;Filiberto and Dasgupta, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…In this section, analyses of a suite of ultramafic rocks similar to those identified on Mars (Poulet et al 2009;Ehlmann et al 2009) are shown. We evaluated the ability of the Terra Fig.…”
Section: Ultramafic Rocksmentioning
confidence: 92%